2015
DOI: 10.1002/ente.201500217
|View full text |Cite
|
Sign up to set email alerts
|

Fuel Electrode Carbon Corrosion in High Temperature Polymer Electrolyte Fuel Cells—Crucial or Irrelevant?

Abstract: In this study the cause and effect of fuel electrode carbon corrosion in high temperature polymer electrolyte fuel cells are highlighted for the first time. Here, measurements of the CO2 concentration in the fuel electrode effluent and spatially resolved current mapping suggest that the reverse‐current decay mechanism, which is responsible for the well‐known air electrode carbon corrosion, is not responsible for the observed fuel electrode carbon corrosion. We propose a chemical carbon oxidation mechanism, cau… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
22
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 19 publications
(28 reference statements)
1
22
1
Order By: Relevance
“…Similar to the cathode catalyst layer, all CV features gradually decrease over the course of SUSD aging. As reported by Engl et al for high temperature phosphoric acid fuel cells, 18 this ECSA-loss can be attributed to the passage of H 2 /air fronts through the anode compartment during SUSD. This change of gas atmosphere effectively results in a step-change of the anode potential from the OCP under H 2 (0 V) to the OCP in air (≈1.05 V in the case of a PEMFC) 24 during shut-down and vice versa during start-up.…”
Section: Resultssupporting
confidence: 59%
See 1 more Smart Citation
“…Similar to the cathode catalyst layer, all CV features gradually decrease over the course of SUSD aging. As reported by Engl et al for high temperature phosphoric acid fuel cells, 18 this ECSA-loss can be attributed to the passage of H 2 /air fronts through the anode compartment during SUSD. This change of gas atmosphere effectively results in a step-change of the anode potential from the OCP under H 2 (0 V) to the OCP in air (≈1.05 V in the case of a PEMFC) 24 during shut-down and vice versa during start-up.…”
Section: Resultssupporting
confidence: 59%
“…However, Engl et al recently showed that SUSD in high temperature phosphoric acid fuel cells leads to significant amounts of carbon corrosion on the anode, along with a loss of Pt electrochemical surface area (ECSA), a finding which the authors attributed to the change of the anode potential upon switching the gas atmosphere between H 2 and air. 18 To the best of our knowledge, no study apart from our previously published ECS Transaction exists that is mainly focused on the degradation of the anode in low-temperature PEMFC systems. 19 While the performance decay from SUSD-induced anode degradation is rather negligible compared to cathode degradation when high anode loadings are used (≥100 μg Pt cm −2 ), it may start to become significant in future PEMFC systems, for which ultra-low anode loadings (≈25 μg Pt cm −2 ) and the use of more stable graphitized cathode carbon supports are envisaged in combination with system mitigation strategies which restrict the occurrence of H 2 /air front events to room temperature, where cathode carbon support oxidation is strongly suppressed.…”
mentioning
confidence: 99%
“…Moreover, the corrosion is accelerated under abnormal conditions like cell reversal, fuel starvation and sudden current transitions [26]. Recent investigations have also individuated an important corrosion phenomena at the anode side in transient operating conditions of fuel feeding [27]. The corrosion rate of carbon materials increases with their surface area, carbon disordering degree and with a high percentage of labile surface carbon moieties [28,29].…”
Section: Introductionmentioning
confidence: 99%
“…[1][2] In addition to their contribution to fundamental research, such studies are also important for developing technologies like fuel cells and metalair batteries. [5][6] Later on, a substantial study on the active center and the reaction mechanism over metal-electrolyte interface has led to significant improvements in the stability and performance of the catalysts. [3][4] Despite their remarkable performance, these catalysts had limited technological implications as their high cost and poor stability posed considerable difficulty.…”
Section: Introductionmentioning
confidence: 99%
“…[3][4] Despite their remarkable performance, these catalysts had limited technological implications as their high cost and poor stability posed considerable difficulty. [5][6] Later on, a substantial study on the active center and the reaction mechanism over metal-electrolyte interface has led to significant improvements in the stability and performance of the catalysts. Also, several alloys of Pt with non-noble metals like Co, Ni, and Fe, with reduced Pt loading have been demonstrated to show enhanced activity.…”
Section: Introductionmentioning
confidence: 99%